The Relevance of the Value of Religious Moderation in the World of Contemporary Indonesian Islamic Education - Aziz, Abdullah; Maulida, Ghina Rahmah; Munawarsyah, Muzawir; Khoiriyati, Wildatun Rizka; Mutiya, Khoiru (AJIS: Academic Journal of Islamic Studies, 2024)
Religious moderation is one of the teachings of Islam as stated in the Qur'an. It should be noted that moderation is a middle attitude without discrimination, intervention or one-sidedness which contains moderate, fair and balanced ideas in all aspects of life, whether religious, social, educational, cultural, and others. Moderate attitudes are important to instill in the nation's generation as early as possible. Given that Indonesia is a country whose society is plural and multicultural, it is not surprising that there are diverse differences. Moderate attitudes need to be instilled to maintain the integrity of relationships both individually, in groups and in the state. Recently, Indonesia has been bombarded with issues about religion, such as blasphemy, hate speech, discrimination of minority communities, extreme groups and others. With this, it certainly threatens the integrity and peace in Indonesia. An alternative path that can be used is through Islamic education. Islamic education is a relevant early solution to understand the meaning of tolerance, justice, harmony, balance and love of peace. This research will explain the meaning of religious moderation using descriptive qualitative methodology with library research studies sourced from books, journals and the Qur'an. The results of this study indicate that there is a development in terms of human character to become a moderate and reactive human being.